Pengembangan Media Smart Land Untuk Meningkatkan Kemampuan Berpikir Kreatif Dalam Penerapan 3CM Learning Untuk Peserta didik Sekolah Dasar - Wahyudi Wahyudi; Dian Nuryani; Yohana Setiawan (Scholaria: Jurnal Pendidikan dan Kebudayaan, 2022)
The purpose of this research is to develop and test the validity, practicality, and effectiveness of Smart Land media to enhance creative thinking skills in 3CM Learning for elementary school students.The method of this research is R&D using ADDIE model, in five steps: 1) analysis, 2) design, 3)development, 4)iImplementation, 5) evaluation. The validity of product test is observed from the expert’s assessement using the material and media expert validation sheet instruments. The effectiveness of the product is observed by the one group pre-test, post-test, and the result are processed using Paired-Samples T-Test assistance with SPSS 22.0 program. The result of this research suggests Smart Land media learning to enhance creative thinking skills in 3CM Learning for Elementary School students, which is evidently valid from materials and media aspect. Smart Land media is evidently practical from teacher and student evaluation, and also evidently effective based on result of pretest and posttest and Paired Samples T-test.